A Comparative 6-Month Clinical Study of Acellular Dermal Matrix Allograft and Subepithelial Connective Tissue Graft for Root Coverage - S. Sadat Mansouri; N. Ayoubian; M. Eslami Manouchehri (Tehran University of Medical Sciences, 2010)
Objective: Different surgical procedures have been proposed for the treatment of gingival recessions. The goal of this study was to compare the clinical results of gingival recession treatment using Subepithelial Connective Tissue Graft and an Acellular Dermal Matrix Allograft. Materials and Methods: The present study was performed on 5 patients with 9 bilateral Miller`s class I or II gingival recessions. This included 15 premolars and 3 canines. In each patient the teeth were randomly divided in two groups of test (ADMA) and control (SCTG). Clinical parameters including recession height (RH), recession width (RW), keratinized gingiva (KG), clinical attachment level (CAL) and probing depth (PD) were measured at baseline, 2, 4 and 6 months after surgery and data analysis was performed using the Wilcoxon signed rank test. Results: The mean changes (mm) from baseline to 6 months in SCTG and ADMA were 2.22±0.83 and 1.77±0.66 decrease in RH, 2.55±0.88 and 2.33±0.86 decrease in RW, 1.44±0.88 and 2.0±1.11 increase in KG, 2.33±1.22 and 2.11±0.6 decrease in CAL and finally 0.22±0.66 and 0.33±0.7 decrease in PD, respectively. The differences in mean changes were not significant between the two groups in any of the parameters. The percentage of root coverage was 85.7% and 71.1% for the control and test group, respectively. The changes from baseline to the 6 month visit were significant for both groups in all parameters but PD. Conclusion: Alloderm may be suggested as an acceptable substitute for connective tissue graft considering the root coverage effect and KG width increase.